A TRAJETÓRIA DE MADRE BASILEA SCHLINK: GÊNERO, RELIGIÃO E AUTORIA FEMININA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The amount of written book by Mother superior Basilea, can express a woman trajectory, that used a religeous life and the female authory written as a tool to have a free opinion and could develop her critical thoughts. She showed off because the Woman Religeous sisterrhood founded in Germany,1947; nowadays has seveveral in many parts of the World. The Evangelica Sisterhood of Maria, interdominational way of the Kanaan ministery in Brazil arrived in 1980, in Curitiba and works nowadays. Since then, works with their own graphic, producing and giving their own founded books. We will show some relevants aspects about Mother Superior Basilea, linking Gender analisys, beginning with her work in the Religeous area and using her written as a research, pointing her autobiography "I found the key to God´s heart". So, the mainly goal for this research is between methodology and the biographic literature about Sister Superior Basilea, understanding her trajectory and her written, her role as a female author. It has as a goal, understanding the literature influence in Maria´s sisters dayly routine with this material. Knowing the production process of the literature in Brazil, by Maria´s sisters work in graphics, like development of the books as object and caracteristics. With this research, we can understand the female written and the religeous life and their contribution that Sister Superior Basilea could build a concept about herself, choosing her own way, and giving up of historical and social standards forced to woman in those ages.
Keywords: autobiografia; autoria feminina; gênero; religião; autobiography; female author; gender; religeous; CNPQ::CIENCIAS HUMANAS::HISTORIA